Ubiquitin-specific protease 11 Aggravates Ischemia-reperfusion-induced Cardiomyocyte Pyroptosis and Injury by Promoting TRAF3 Deubiquitination - Yunfei Zhang; Juledezi Hailati; Xiaoyun Ma; Hasidaer Midilibieke; Zhiqiang Liu (Balkan Medical Journal, 2023)
Background: In myocardial ischemia-reperfusion injury, myocardial damage is aggravated when blood perfusion is restored in myocardial infarction. Ubiquitin-specific protease 11 (USP11), a deubiquitinating enzyme, could remove the ubiquitination of substrate proteins and regulate protein stability, thereby affecting multiple pathological processes. Aims: To investigate the potential function of USP11 in myocardial ischemia-reperfusion injury and its underlying mechanisms. Study Design: In vivo and in vitro experimental study. Methods: The ischemia-reperfusion rat model in vivo was evolved, wherein the left anterior descending coronary artery was ligated for 30 min, followed by ligature release for 120 min. Meanwhile, H9C2 cells were brought to hypoxia for 6 h and then reoxygenated for 18 h to establish a cell hypoxia-reoxygenation (H/R) injury in vitro. Then, the loss-of-function experiments of USP11 were performed. Triphenyltetrazolium chloride and hematoxylin and eosin staining were performed to observe myocardial injury. The MTT assay was utilized to detect H9C2 cell viability. Pyroptosis was analyzed by TUNEL staining and flow cytometry. Pyroptosis-related protein expression and TRAF3 were analyzed via Western blot. The content of inflammatory factors was examined by enzyme-linked immunoassay. Co-immunoprecipitation and ubiquitination assays were performed to analyze for USP11 interacting with TRAF3. Results: USP11 was upregulated in the ischemic heart tissue. Ischemia-reperfusion and H/R injuries increased USP11 expression. USP11 loss-of-function assays showed that USP11 knockdown alleviated ischemia-reperfusion- and H/R-induced myocardial cell damage, pyroptosis, pro-inflammatory factor secretion, and IKKβ/NF-κB pathway activation. In H9C2 cells, USP11 stabilized TRAF3 by deubiquitination. Furthermore, rescue experiments revealed that TRAF3 overexpression reversed the protection of silencing USP11 on H/R-induced H9C2 cell injury. Conclusion: This study confirmed that USP11 knockdown ameliorated myocardial ischemia-reperfusion injury by downregulating TRAF3, suggesting that USP11 silencing can be a novel target of myocardial infarction.